Reflections of the Japanese Education System in Britain A Modern Utopia? 1858-1914. - Hiraoka, Mari. (New York, USA Routledge, 2024)
This book explores British reflections of Japanese education between 1858 and 1914, by referring to accounts by British observers, derived from documentary sources such as newspapers, journal articles, published books, and official reports. Hiraoka argues that British attitudes and comments on Japanese education reflect concerns about their own education system. International economics and politics of the time, as well as the voices of the Japanese, are also taken into account. British interpretations of the advantages of Japanese education are explained with two seemingly contradictory views: traditions inherited in Japan, and modern institutions newly introduced using the Western model. The book illustrates how this dual view of Japan affected the rise and fall of British interest in Japanese education over half a century. It also explores a broad range of phenomena - educational reforms, legislation and practice, science networks, exhibitions, international trade, and military affairs - to observe how Japanese education was viewed by the British. It consults a wide range of primary sources, most of which are published or digitally archived. Shedding new light on the transnational history of the educational relationship between Japan and Britain, this book will be an attractive base for future researchers in the fields of history of education, cultural history, and comparative education.
Keywords: EDUCATION / Comparative; HISTORY / Asia / Japan; Education -- Great Britain -- Japanese influences; Education -- Japan -- History; Comparative education